Implementace 3D tisku do vzdělávání na FPE ZČU v Plzni - KROTKÝ, Jan (Journal of Education, Technology and Computer Science, 2014)
The author describes the solutions and the results of the implementation of 3D printers at schools in the UK. He summarizes the conclusions of the British project. The author then describes the current state of the same issues in the Czech Republic and presents his own experiences and recommendations. The analysis of the state is divided into the formal and non-formal education because their concepts are different. In conclusion, the author defines questions for the other solving of the implementation of 3D printing at schools